Kebijakan Pertahanan Berbasis Ancaman: Menilai Dampak dan Efektivitasnya - Sarjito, Aris (Institut Riset dan Publikasi Asas Nusantara., 2024)
Threat-based defense prioritizes policies specific threats to enhance national security and resource allocation. This research aims to assess the impact and effectiveness of such policies using qualitative methods and secondary data. The study employs secondary data sources, including government reports, strategic documents, and academic articles, to explore three key aspects: the effectiveness of threat-based defense policies, the critical factors influencing their successful implementation, and the potential drawbacks and unintended consequences. Findings indicate that threat-based policies improve national security by focusing resources on high-priority threats but can lead to threat inflation and the neglect of non-prioritized threats. Key factors for successful implementation include accurate intelligence, advanced technologies, and strong political and military leadership. However, unintended consequences such as strained international relations and escalating arms races highlight the complexity of these policies. The study concludes that while threat-based defense policies offer targeted improvements, they must be managed carefully to avoid negative outcomes. The findings emphasize the need for a balanced approach, integrating threat-based strategies with broader security measures to ensure comprehensive national defense.